Cell Death in the Developing Brain after Hypoxia-Ischemia - Thornton, Claire; Leaw, Bryan; Mallard, Carina; Nair, Syam; Jinnai, Masako; Hagberg, Henrik (Frontiers in Cellular Neuroscience, 2017)
Perinatal insults such as hypoxia–ischemia induces secondary brain injury. In order to develop the next generation of neuroprotective therapies,we urgently need to understand the underlying molecular mechanisms leading to cell death. The cell death mechanisms have been shown to be quite different in the developing brain compared to that in the adult. The aim of this review is update on what cell death mechanisms that are operating particularly in the setting of the developing CNS. In response to mild stress stimuli a number of compensatory mechanisms will be activated, most often leading to cell survival. Moderate-to-severe insults trigger regulated cell death. Depending on several factors such as the metabolic situation, cell type, nature of the stress stimulus, and which intracellular organelle(s) are affected, the cell undergoes apoptosis (caspase activation) triggered by BAX dependent mitochondrial permeabilsation, necroptosis (mixed lineage kinase domain–like activation), necrosis (via opening of the mitochondrial permeability transition pore), autophagic cell death (autophagy/Na+,K+-ATPase), or parthanatos (poly(ADP-ribose) polymerase 1, apoptosis-inducing factor). Severe insults cause accidental cell death that cannot be modulated genetically or by pharmacologic means. However, accidental cell death leads to the release of factors (damage-associated molecular patterns) that initiate systemic effects, as well as inflammation and (regulated) secondary brain injury in neighboring tissue. Furthermore, if one mode of cell death is inhibited, another route may step in at least in a scenario when upstream damaging factors predominate over protective responses. The provision of alternative routes through which the cell undergoes death has to be taken into account in the hunt for novel brain protective strategies.